Kajian Tipologi Sufiks –an dalam Bahasa Indonesia - Suryadi, M (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
In Indonesian language, the study of suffix “–an” has been widely practiced by linguists, as if the study of suffix “–an” has been completed and there was no problem. Behind that, the rule of certainty about the suffix “–an” has not been convincingly revealed, wheater it is related to necessity, probability, and certainty.Through typology studies can be found the rules of certainity suffix “–an”. Surely, there will be found three rues: first the rule of suffix “–an”, second the rule of stability of the suffix “–an”, and third the rule of the suffix “–an” position on the sentence relation. Further findings on setencial relations: the presence of the suffix -an determined by verbal form. In relation S-V-O suffix -an always occupy the argument. Suffix -an have the ability to change all categorical word into a noun category except the category of adverbs.